GEOELECTRICAL MODEL OF GEOTHERMAL SPRING IN IE JUE SEULAWAH DERIVING FROM 2D VLF-EM AND DC RESISTIVITY METHODS - Marwan, Marwan; Isa, Muhammad; Idroes, Rinaldi; Nursyafira, Nursyafira; Idris, Syafrizal; Yanis, Muhammad; Abdul Ghani, Azman; Yadi Paembonan, Andri (Journal of Applied Engineering Science, 2022)
Seulawah Agam is one of the volcanic areas in Aceh province, Indonesia, which planned for a powerplant constriction with an energy capacity expected to be approximately 230 MWe. This volcano has seven manifestations in the form of craters, hot water, and heated soil. The hydrothermal system in this volcano is controlled by a fault system which acts as a medium for the entry and exit of fluids. Therefore, understanding the local geology is required for geothermal power plant development, especially for the determination area for injection and production wells. In this research, we use the Very Low-Frequency Electromagnetic (VLF-EM) methods combined with electrical resistivity tomography data on the Ie Jue manifestation area to determine the shallow structure related to the manifestation. The VLF was made for 4 profiles with 700 m length for each VLF-EM profile and 300 m for electrical resistivity lines. We utilized the Karous Hjelt filter for qualitative interpretation, while Occam's algorithm was applied for 2D inversion of data for quantitative analysis of VLF-EM data. Based on the current density model, several vertical conductive anomalies can be well demonstrated at a distance of 300-400 m from the four VLF profiles. The conductive anomaly can also be seen in the resistivity data from the electrical resistivity. The results of the Occam model show that the depth of faults and fractures is seen at 30 m depth with low resistivity (below 100 Ωm). This anomaly is generally associated with outcrops in the field, such as fumarole and warm ground on the east side of the manifestation area. In addition, the 2D inversion model of VLF also shows the contrast of several fracture zones as a place for fluid to enter and exit the Seulawah volcano. Therefore, based on our result, it can be summed up that this method is effectively applied to geothermal in high terrain areas such as in Indonesia and can be used to suggest safe locations for injection wells and production of geothermal drilling.
Keywords: very low frequency, 2D inversion, hot spring, Seulawah Agam